2010
DOI: 10.2139/ssrn.1669173
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Secularization: Cultural Transmission, Religion and Fertility Theory, Simulations and Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…1 Previous research on individual-level affiliation and fertility showed that although exogenous factors matter and can overcome demographic limitations, endogenous growth is foundational to large-scale changes in the religious landscape over time (Hout et al 2001;Kaufmann 2010;Stark 1996Stark , 2005. Children do not always adopt their parents' religion and can even rebel against it, but parents' religion is the strongest predictor of children's religion, and religious switching is shaped by the religious composition of the society in which it occurs (Bar-El et al 2013;Iannaccone 1998;Kelley and Graaf 1997;Sherkat and Wilson 1995). Specifically, when vertical cultural transmission from parent to child breaks down and switching occurs, horizontal cultural transmission determines the types of new religious beliefs and preferences people adopt Verdier 2000, 2011).…”
Section: Secularization Fertility and Religious Populations Over Timementioning
confidence: 99%
“…1 Previous research on individual-level affiliation and fertility showed that although exogenous factors matter and can overcome demographic limitations, endogenous growth is foundational to large-scale changes in the religious landscape over time (Hout et al 2001;Kaufmann 2010;Stark 1996Stark , 2005. Children do not always adopt their parents' religion and can even rebel against it, but parents' religion is the strongest predictor of children's religion, and religious switching is shaped by the religious composition of the society in which it occurs (Bar-El et al 2013;Iannaccone 1998;Kelley and Graaf 1997;Sherkat and Wilson 1995). Specifically, when vertical cultural transmission from parent to child breaks down and switching occurs, horizontal cultural transmission determines the types of new religious beliefs and preferences people adopt Verdier 2000, 2011).…”
Section: Secularization Fertility and Religious Populations Over Timementioning
confidence: 99%
“…According to the author's best knowledge, Bar-El et al (2013) is the first contribution that analyzes the evolution of secular/religious cultural traits in a framework of endogenous cultural transmission. Their central focus is the difference in the taste for children between two types of individuals and how the resulting difference in fertility rates affects the diffusion pattern of religiosity in the population.…”
Section: Related Literaturementioning
confidence: 99%
“…Through this process, children acquire preferences for civil liberties either from their paternalistic parents' socialization efforts or through contacts with random ''role models'' from the entire population. The evolutionary process of secularization is studied in Bar-El et al (2013), which also applies the framework of Bisin and Verdier (2001). However, in addition to families and society, we assume that the government can intervene in this socialization process through the contents of a school education and that this public intervention is politically determined by political regimes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous research on individual-level religious affiliation and fertility showed that while exogenous factors are important and can overcome demographic limitations, endogenous growth is foundational to large-scale changes in the religious landscape over time (Hout et al 2001;Kaufmann 2010;Stark 1996Stark , 2005. Children do not always adopt the religion of their parents and sometimes even rebel against it, but parents' religion is the strongest predictor of children's religion, and religious switching is influenced by the religious composition of the society in which it occurs (Bar-El et al 2013;Iannaccone 1998;Kelley and Graaf 1997;Sherkat and Wilson 1995). Specifically, when vertical cultural transmission from parent to child breaks down and switching occurs, horizontal cultural transmission determines the types of new religious beliefs and preferences people adopt Verdier 2000, 2011).…”
Section: Secularization Fertility and Religious Populations Over Timementioning
confidence: 99%